DEVELOPING MATHEMATICAL IMAGINATION IN PRESCHOOL CHILDREN THROUGH GAMES - Latofat Botirova; Dilnoza Pirnazarova (Scholars Digest Publishing, 2024)
This article delves into the importance of utilizing mathematical games and activities to develop mathematical imagination in preschool-aged children. It examines effective strategies for implementing these tools in educational settings, emphasizing the establishment of a dedicated mathematics corner within the group room to encourage interactive learning. Furthermore, the paper outlines methods for fostering collaboration with parents to support the child's mathematical development at home. By integrating games, practical tasks, and parental involvement, the study underscores the role of engaging approaches in shaping foundational mathematical concepts and enhancing preschoolers' cognitive and imaginative abilities.
Keywords: mathematical games and tasks, organization of a mathematics corner, cooperation with parents, mathematical calculations, mathematical knowledge, cognitive functions, competitive games.